2007
DOI: 10.1016/j.jacc.2007.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Morphologic Characteristics and Local Temperature Differences in Culprit Lesions of Patients With Symptomatic Coronary Artery Disease

Abstract: The present study showed that culprit lesions with plaque rupture and positive arterial remodeling have increased thermal heterogeneity, although in certain patients a discrepancy between morphogic and functional characteristics was observed. A combination of morphologic and functional examination may offer additional diagnostic and prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 39 publications
(56 reference statements)
0
25
0
7
Order By: Relevance
“…Some preliminary data were also obtained with temperature sensors based on thermocouples [10][11][12][13]. In addition, the presence of this thermal heterogeneity, also referred to as ''hot spots'' or ''hot plaques'', has been shown to be present more often in unstable lesions [4], to be associated with poor clinical outcome [5], to be improved with statins [6], and to be correlated with plaque morphology characteristics [7] and with serum concentration of systemic inflammation markers (CRP, IL-6) [8]. Most of this data has been obtained with a thermistor-based resistance [3][4][5][6][7][8][9], of which the signal is possibly also influenced by changes in pressure and/ or flow.…”
Section: Introductionmentioning
confidence: 99%
“…Some preliminary data were also obtained with temperature sensors based on thermocouples [10][11][12][13]. In addition, the presence of this thermal heterogeneity, also referred to as ''hot spots'' or ''hot plaques'', has been shown to be present more often in unstable lesions [4], to be associated with poor clinical outcome [5], to be improved with statins [6], and to be correlated with plaque morphology characteristics [7] and with serum concentration of systemic inflammation markers (CRP, IL-6) [8]. Most of this data has been obtained with a thermistor-based resistance [3][4][5][6][7][8][9], of which the signal is possibly also influenced by changes in pressure and/ or flow.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is enhanced during the destabilization of AP [19]. In recent studies, surface thermometry of AP has showed direct correlation between unstable plaques and level of inflammation markers [20].…”
Section: Resultsmentioning
confidence: 99%
“…Another study using thermography and IVUS has shown that the site with the highest temperature is distal to the angiographically most stenotic site [37], accurately localizing the culprit lesion. Furthermore, combined plaque assessment by IVUS and thermography has shown that plaques with expansive remodeling and ruptured plaques are associated with increased local inflammatory activation, as demonstrated by an increased temperature difference [38]. The use of thermography for vulnerable plaque detection is limited due to the cooling effect of blood flow that causes underestimation of temperature differences and due to the need for the tip of the catheter to be in contact with the vessel wall being studied [39], which could lead to vessel damage.…”
Section: Invasive Imaging Modalitiesmentioning
confidence: 99%